Radiometric localisation of partial discharge sources inside Air‐insulated electrical substation. Issue 8 (1st October 2019) - Kumar Mishra, Dipak; Bhukya, Anitha; Koley, Chiranjib; Kumar Roy, Nirmal
Abstract : Monitoring partial discharge (PD) activities inside electrical substation using few ultra high frequency (UHF) sensors mounted around the periphery of the substation could be a useful and economical tool. In this work, an experimental study has been conducted in the laboratory and in substations to investigate the localisation ability of the UHF PD detection system. For localisation, one needs to calculate time difference of arrivals (TDOAs) between the UHF waveforms obtained from the multiple sensors mounted around the substation. After that these TDOAs are used for localisation of the PD sources. In this paper a novel joint entropy (JE)‐based TDOAs calculation method is proposed and also compared with the existing techniques. For localisation of PD sources, a modified direction of arrival (DOA)‐based method for the near field is proposed, as found to be suitable when the sensors are mounted around the substation. Obtained results in TDOA estimation using the proposed JE method is in line with other technique; however, it was found to provide consistent results and is useful in an extreme situation. Modified DOA‐based localisation algorithm found to provide improved performance due to the elimination of approximation as required in previously reported far‐field‐based localisation system for the air‐insulated substations.